Analytical landau-type model of polarization switching in ferroelectrics - Chew, Khian Hooi; Ong, L.H.; Loh, K.K. (2013)
The polarization switching properties of ferroelectric materials have been extensively studied, both experimentally and theoretically owing to their wide applications in industry and hence generating a need to gain a deeper understanding of factors affecting their switching behaviour. In this paper, an analytical Landau theory incorporating the Landau-Khalatnikov equation has been developed to describe the switching properties of second order ferroelectrics. Analytical expressions derived from exact results of Landau theory are used in modelling work carried out in this study for comparison with trends predicted by empirical laws used to describe polarization switching behaviour at high electric fields. As such this work has established the theoretical basis for empirical laws of polarization switching and developed simple numerical tools which can be quickly used to model trends in polarization switching behaviour of ferroelectrics. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.